In Pursuit of Inclusion: Studying the Impact of EDI Policies in the Workplace and Exploring the Challenges of Measurement - Garakani, Tatiana; Nzobonimpa, Stany; Mbengue-Reiver, Marie-Andrée (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2023)
As part of this study, we developed a survey in which we focus on employees’ experience of inclusion in their workplaces. We assessed the impact of equity, diversity, and inclusion (EDI) policies on the respondents’ perceptions of the workplace. Our results indicated that organizations with EDI policies are more likely to be perceived as positive work environments. Moreover, we find that the perception of the workplace differs according to individuals and their identities. These results confirm, on the one hand, that the development of EDI policies is worthwhile. On the other hand, employers must pay more attention to their employees’ experiences in order to better understand their realities, particularly with regard to the various identities (perceived, real or supposed) and associated stigmas and stereotypes. The narrative component of our survey provides an overview of elements that are critical to understanding the issues that we investigated, but that are often missing from traditional surveys.